Variation of grain iron content in a local upland rice germplasm from the village of Huai Tee Cha in northern Thailand - Saicum Pintasen (2018)
This experiment examined variation of iron (Fe) concentration in grain of local Thai rice varieties from Huai Tee Cha village, in northern Thailand. Seeds of 17 named varieties were collected from farmers in 66 accessions. Brown rice from each accession was stained individually with Perls' Prussian blue, with IR68144 (high grain Fe) and KDML105 (low grain Fe) as checks. A wide range of grain Fe contents were found among different varieties, different seed lots with the same name and within individual accessions, notably BB, BGU and BK. The Fe concentrations in these varieties were confirmed by chemical analysis. Two accessions of each variety with most intense staining and highest average concentration of grain Fe were selected, and 20-40 seeds from each were sown for subsequent progeny testing. There was morphological variation between plants in 5 out of 6 accessions in characteristics such as pigmentation of the apiculus, pericarp and seed coat, while the sixth was externally uniform. Analysis for Fe concentration in seeds of individual lines found that the highest Fe lines were 40% to 50% higher than the lowest Fe lines. This range of grain Fe was found in all six accessions that were progeny tested, including BGU5 which was externally uniform in appearance (H′ = 0). We have shown that variation in grain Fe concentration in local Thai rice may be found between different seed lots bearing the same name and within individual seed lot as well as between varieties. This level of genetic variation may need to be considered when assessing for traits such as grain Fe for breeding programs. © 2007 Springer Science+Business Media B.V.